Apparatus for Early Detection of Respiratory Diseases Aggravated by Respiratory Failure and Apnea-Hypopnea Syndrome - O. B. Zelmanski; V. A. Bogush (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Since loss of working capacity and disability associated with respiratory diseases are caused by bronchial asthma and chronic obstructive pulmonary disease in 2/3 of cases, there is a need for technical support for early detection of these diseases. The developed diagnostic complex is based on an evolutionary mathematical model of the human respiratory system, describing the processes of gas exchange between the atmosphere and the lungs and between the lungs and blood. The complex allows analyzing such respiratory system parameters as arterial blood hemoglobin oxygen saturation, heart rate and respiratory rate. The complex is suitable for onetime (screening) measurements, as well as long-term (night/daily) monitoring. The corresponding software has been developed that allows analyzing the desaturation index, apnea-hypopnea index, photoplethysmogram, and visualizing the breathing process. The complex implements a standardized six-minute walk load test. This allows identifying respiratory failure, assessing its severity and conditions of occurrence. During the testing at a health resort, it was possible to diagnose obstructive apnea-hypopnea syndrome at an early stage in people who were unaware of the disease. The choice of a health resort was due to the comfortable conditions for conducting night monitoring, the availability of time and the desire of people to take care of their health and undergo diagnostics.